What teachers and parents can add to personality ratings of children: Unique associations with academic performance in elementary school. Issue 6 (November 2021) - Brandt, Naemi D; Becker, Michael; Tetzner, Julia; Brunner, Martin; Kuhl, Poldi
Adults' ratings of children's personality have been found to be more closely associated with academic performance than children's self-reports. However, less is known about the relevance of the unique perspectives held by specific adult observers such as teachers and parents for explaining variance in academic performance. In this study, we applied bifactor (S–1) models for 1411 elementary school children to investigate the relative merits of teacher and parent ratings of children's personalities for academic performance above and beyond the children's self-reports. We examined these associations using standardized achievement test scores in addition to grades. We found that teachers' unique views on children's openness and conscientiousness had the strongest associations with academic performance. Parents' unique views on children's neuroticism showed incremental associations above teacher ratings or self-reports. For extraversion and agreeableness, however, children's self-reports were more strongly associated with academic performance than teacher or parent ratings. These results highlight the differential value of using multiple informants when explaining academic performance with personality traits.